DETERMINAN KINERJA INDIVIDU: SISTEM INFORMASI AKUNTANSI DAN TEKNOLOGI INFORMASI - Saifudin, Saifudin; Mayangsari, Nur'aini (Solusi, 2022)
This study's purpose is to understand the accounting information system effectiveness, the use of information technology, the technological sophistication, and   the participation of management towards Bank Jateng Kantor Pusat's individual performance. The methods that being used in this study are survey method and Questionnaire method using Likert scale. Data used in this research are primary data and the sampling was done by the purposive sampling method. Hypothesis test used mulptiple liner regression analysis.                       In addition, analysis method that being used is Linear Regression Method. The result shows that individual performance is much affected by the effectiveness and reliability of the AIS system. And the use of information technology and the technological sophistication doesn t affect on the individual performance. The F test shows that independent variables are simultaneously gives impact on individual performance. The t test shows a significant effect towards individual performance with significance rate of 0,001 for the use of information technology accounting information system effectiveness, 0,266 for the use of information technology, 0,351 for the technological sophistication and 0,002 for participation of management